Efecto de las densidades de siembra en el rendimiento de la asociación maíz-frijol voluble (1992)
In the cold climate zones of the country, the practice of associated crops is widely utilized. In the Departments of Boyac, Cundinamarca and Nariflo, the association maize with vine beans occupies an area close to 40.000 ha, almost always planted at low densities and using regional varieties. This study was conducted at Tibaitatá, ICA Research Center, located at Mosquera (Cundinamarca, Colombia) at 2540 mast and 13 grados centigrados, as average temperature to determine crop yields as affected by plant densities. Commercial varieties of vine beans "Sangretoro' and Maize "ICA V- 25 504' were planted simultaneaously, using a square pattern of 92 cm. Bean yield was (1055 and 777 kg per ha) greater when two plants were established per site than when one bean plant was sown; in contrast, maize yield was slightly lower when planted in association with two bean plants than when only one maize plant was present (5193 and 5634 kg per ha respectively). As maize plant density increased from 2 to 3, to 4 plants per site, yields increased significantly from 2865 to 6847 kg per ha respectively; while the bean yields, utilizing the same above plant densities, decreased from 1058 to 875 kg per ha. Four maize plants, with two bean plants (4 x 2), gave the highest land efficiency use index (1.54), is considered to be the best association for these two species of plants.